2015
DOI: 10.1016/j.jpeds.2015.06.067
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Magnesium and Cerebral Palsy in Preterm Infants

Abstract: Objective To evaluate the relationship of maternal antenatal magnesium sulfate (MgSO4) with neonatal cranial ultrasound abnormalities and cerebral palsy (CP). Study design In a randomized trial of MgSO4 or placebo in women at high risk of preterm delivery, up to three cranial ultrasound were obtained in the neonatal period. Images were reviewed by at least two pediatric radiologists masked to treatment and other clinical conditions. Diagnoses were predefined for intraventricular hemorrhage (IVH), periventric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 37 publications
1
21
0
1
Order By: Relevance
“…The preventive effect on CP was only partly mediated by a reduction in cranial ultrasound abnormalities in the neonatal period [19]. Maternal treatment with a β-blocker and MgSO 4 has been shown to alter neonatal cerebral hemodynamics which may modify the risk of IVH [20].…”
Section: Discussionmentioning
confidence: 99%
“…The preventive effect on CP was only partly mediated by a reduction in cranial ultrasound abnormalities in the neonatal period [19]. Maternal treatment with a β-blocker and MgSO 4 has been shown to alter neonatal cerebral hemodynamics which may modify the risk of IVH [20].…”
Section: Discussionmentioning
confidence: 99%
“…46 A recent study has shown that antenatal magnesium sulfate is associated with a reduced risk of white matter echolucencies and echodensities on cranial ultrasound; however, this effect only partially explains the reduction of cerebral palsy among exposed newborns. 7 Antenatal exposure to magnesium sulfate has not been associated with a reduction in brain injuries known to cause cerebral palsy, such as cystic white matter injury or intraventricular hemorrhage (IVH), in several randomized controlled trials that used ultrasound to diagnose brain injury. 812 The underlying explanation for the neuroprotective effects of magnesium sulfate in premature newborns is unclear, and further investigation for brain injury with magnetic resonance imaging (MRI) may help clarify this.…”
mentioning
confidence: 99%
“…We were unable to reliably collect data about them during the early phases of their implementation and therefore have not included them in our data set. However, as of this time, neither antenatal Magnesium (38, 39) nor delayed cord clamping (40) has been shown to alter the incidence of severe IVH in preterm infants. It is possible that our study was underpowered to detect small differences in neonatal outcomes; the number of infants that delivered ≥10 days after the first dose of BMZ was small and the cohort that received a second course of steroids was even smaller.…”
Section: Discussionmentioning
confidence: 98%